Evaluation of Mass Drug Administration to Eliminate Lymphatic Filariasis in Surguja and Surajpur District, Chhattisgarh - Mendhe, Harshal Gajanan; Prasad, Manish A; Potdar, Pralhad; Verma, Akash (Indian Journal of Community Health, 2022)
Background: Mass Drug Administration of a single dose of DEC was launched on June 5, 2004 by the Government of India. MDA coverage increased gradually from 72.42% in 2004 to 88.96% in 2014. However, compliance has remained relatively low in most of the endemic areas as in 9 endemic Districts in State of Chhattisgarh. In Chhattisgarh State, Lymphatic Filariasis affected 14,818 people in the year 2011 and 13921 in the year 2013 with demonstrated manifestation. Objectives: To assess the coverage and compliance along with factors affecting compliance regarding MDA implementation in Surguja and Surajpur District of Chhattisgarh. Methods: A cross-sectional descriptive study was conducted from July-September 2021 in two district of Chhattisgarh. The division of segments and selection of the households was done based on the WHO criteria of coverage evaluation survey field guide in which from 30 villages, 450 households were covered. Result: The overall coverage rate was 95.55% in Surguja and 89.16% in Surajpur District. The overall compliance was 89.3% with Coverage-Compliance gap of 4.12. The Effective Coverage Rate was 89.3% in 2243 eligible population of Surguja and Surajpur District. Coverage and Compliance was found more in females as compared to males but was found to be statistically not significant. Coverage and Compliance was found more in Surguja district as compared to Surajpur district. Conclusion: Training programme for drug distributors should emphasize more on how to address the fear of side effects among beneficiaries and other reasons of low compliance for the benefit of the MDA programme.